Lutuan ning pamana revitalizing kapampangan culinary heritage through an experiential Culinary Museum and Food Innovation Complex in Clark, Pampanga - Terre, Ernztin Andrea A.; David Xander T. Lacson (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Kapampangan cuisine is increasingly at risk of marginalization due to the rising popularity of global food trends and the lack of culturally grounded platforms that nurture local culinary heritage. To address this concern, this study explores the potential of a Culinary Museum and Food Innovation Complex in Pampanga, the Culinary Capital of the Philippines. The development, which features a culinary museum, food innovation center, and a river park, utilizes experiential and tropical design principles to promote gastronomic tourism, cultural sustainability, and local economic growth. The architectural design was informed by qualitative methods, including the modified Placemaker Method of Marichela Sepe and key informant interviews. Strategically located near the National Food Hub (NFH) Project and Clark International Airport, the development aims to bridge culture, innovation, and commerce. Its layout is divided into three zones to serve diverse user needs: Immersion for food experiences, Collaboration for consumer and expert engagement, and Exploration for food innovation. The design incorporates flexible transition spaces, passive cooling strategies, and vernacular elements to enhance both sustainability and user experience. Anchored on the concept of “Pistang Baryo,” the project celebrates food, culture, creativity, and tourism. By combining innovative spatial strategies with cultural and ecological sensitivity, it offers a platform for both preservation and innovation. In revitalizing Kapampangan culinary heritage, it ensures that as global influences grow, local culinary traditions not only endure but also evolve while proudly staying rooted in their identity.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Culinary heritage facility -- Clark (Pampanga); Food tourism -- Clark (Pampanga)